Economic Aspects of the Development of Human Capital in the Ecosystem - Andrey Poltarykhin, Galina Chernukhina, Elena Udovik, Nadezhda Sukhina, Valentina Varlamova, Mikhail Zavyalov (International Journal of Advanced Science and Technology, 2020)
The article discusses the economic aspects of the development of human capital in the ecosystem. Human capital plays a large role in improving the quality and efficiency of labor in absolutely all spheres of the life of the state. Currently, the environmental component is increasingly being included in the theory of human capital. The composition of human capital includes a health fund, part of which is natural, hereditary, and part - acquired as a result of the expenditure of efforts and resources of a person and of the whole society.